A Paramagnetic Metal‐Organic Framework Enhances Mild Magnetic Hyperthermia Therapy by Downregulating Heat Shock Proteins and Promoting Ferroptosis via Aggravation of Two‐Way Regulated Redox Dyshomeostasis - Yi Wang; Zelong Chen; Jiahui Li; Yafei Wen; Jiaxuan Li; Yinghua Lv; Zhichao Pei; Yuxin Pei (Advanced Science, 2024)
Abstract Mild magnetic hyperthermia therapy (MMHT) holds great potential in treating deep‐seated tumors, but its efficacy is impaired by the upregulation of heat shock proteins (HSPs) during the treatment process. Herein, Lac‐FcMOF, a lactose derivative (Lac‐NH2) modified paramagnetic metal‐organic framework (FcMOF) with magnetic hyperthermia property and thermal stability, has been developed to enhance MMHT therapeutic efficacy. In vitro studies showed that Lac‐FcMOF aggravates two‐way regulated redox dyshomeostasis (RDH) via magnetothermal‐accelerated ferricenium ions‐mediated consumption of glutathione and ferrocene‐catalyzed generation of ∙OH to induce oxidative damage and inhibit heat shock protein 70 (HSP70) synthesis, thus significantly enhancing the anti‐cancer efficacy of MMHT. Aggravated RDH promotes glutathione peroxidase 4 inactivation and lipid peroxidation to promote ferroptosis, which further synergizes with MMHT. H22‐tumor‐bearing mice treated with Lac‐FcMOF under alternating magnetic field (AMF) demonstrated a 90.4% inhibition of tumor growth. This work therefore provides a new strategy for the simple construction of a magnetic hyperthermia agent that enables efficient MMHT by downregulating HSPs and promoting ferroptosis through the aggravation of two‐way regulated RDH.